2016
DOI: 10.1016/j.jclepro.2015.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Information strategy failure: personal interaction success, in urban residential food waste segregation

Abstract: Direct measurements were taken of residential food waste sorting in a sample from over 5000 communities (5 million households) assigned to a pilot program delivered by government branches in Shanghai which relied on an information strategy for implementation. The results are compared to a population of N=36 similar communities (36,000 households) assigned to a different program which involved considerable personal interaction. The results show that the information–based program communities did not noticeably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 53 publications
1
39
0
1
Order By: Relevance
“…The results were also similar: no discernible food waste sorting was found to be taking place [17]. The results of our control group are thus entirely consistent with the results of that wider study.…”
Section: Discussionsupporting
confidence: 91%
“…The results were also similar: no discernible food waste sorting was found to be taking place [17]. The results of our control group are thus entirely consistent with the results of that wider study.…”
Section: Discussionsupporting
confidence: 91%
“…This indicated the importance of studies to provide information for the design and implementation of anti-waste programs. Dai et al (2016) conducted an interesting and meaningful study on domestic waste sorting, the failure of information-based programs and the success of personal interaction. Although it is not directly related to the main scope of this study, it clearly indicated the importance of human factor in the education and behaviours changing initiatives.…”
Section: Causes Of Failure Of Anti-food Waste Programsmentioning
confidence: 99%
“…The 'main message' delivered in the doorstepping was not, therefore, the cause of the impact in this case, which implied that the delivery approach was. Building on this result, a further study is being carried out to determine the average results from a large sample of communities which used information only versus another sample which used interpersonal approaches including some forms of doorstepping (Dai, 2015).…”
Section: Learning Useful For Improving Local Designmentioning
confidence: 99%
“…The programs were initially piloted in 1000 eligible "role model" communities to identify best practices in preparation for the introduction of the program citywide by 2020. The pilot schemes primarily involved the delivery of information, and sometimes involvement of local volunteers (Dai et al, 2015), but almost all with poor results (Huang et al, 2014). Several different alternative approaches are being explored, including involvement of specialist NGOs , extra prompting , incentives, and monitoring and feedback systems.…”
Section: Introductionmentioning
confidence: 99%